PENGGUNAAN LIGHT EMITTING DIODE PADA LAMPU CELUP BAGAN (The Use of Light Emitting Diode on Sunked Lamps of Lift Net) - Imanuel M. Thenu; Gondo Puspito; Sulaeman Martasuganda (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2013)
ABSTRACTLift net fishermen usually use fluorescent lamp as attractor to lure fish. As price of fuel rise, fishermen are forced to find another option to change their attractor into some much lower cost and more energy-save lamp, or in other words, to change into LED lamp. This research are providing evidence that sunked LED lamps can be utilized as a helper tools, and also determined the best time for catching fish in the lift net. Two lift net used in this research, one of them used sunked LED lamps and the other used ordinary fluorescent lamps. Lift net are operated as long as 20 nights, with four catching times per night, between 18.00-21.00, 21.00-00.00, 00.00-03.00, and 03.00-06.00. Results showed that LED lamps give a better result with 11 organisms successfully catch (287,6 kg), compared to ordinary fluorescent lamps with only six organisms (238,3 kg). The best time for catching with LED lamps are between 18.00-21.00 (121 kg), while between 21.00-00.00 (67,4 kg), 00.00-03.00 (46,9 kg) and 03.00-06.00 (52,3 kg).Key words: fluorescent lamp, lift net, light emitting diode, Palabuhanratu,sunked lights-------ABSTRAKNelayan bagan biasa menggunakan lampu fluorescent sebagai atraktor untuk memanggil ikan. Harga bahan bakar yang mahal menyebabkan nelayan harus beralih memakai jenis lampu lain yang hemat energi, seperti lampu LED (light emitting diode) Penelitian bertujuan untuk membuktikan bahwa lampu celup LED dapat digunakan sebagai alat bantu penangkapan ikan pada bagan dan menentukan waktu operasi penangkapan terbaik. Dua bagan digunakan dalam penelitian ini. Masing-masing menggunakan lampu celup LED dan lampu fluorescent. Bagan dioperasikan selama 20 malam. Dalam 1 malam dilakukan 4 kali penangkapan, yaitu antara jam 18.00-21.00, 21.00-00.00, 00.00-03.00 dan 03.00-06.00. Hasil penelitian menunjukkan bahwa penggunaan lampu celup LED pada bagan menghasilkan 11 jenis organisma tangkapan seberat 287,6 kg, atau lebih banyak dari lampu fluorescent sejumlah 6 organisma (238,3 kg). Adapun waktu penangkapan terbaik pada bagan yang menggunakan lampu LED adalah antara pukul 18.00-21.00 yang menghasilkan tangkapan seberat 121 kg, sedangkan 21.00-00.00 (67,4 kg), 00.00-03.00 (46,9 kg) dan 03.00-06.00 (52,3 kg).Kata kunci: lampu fluorescent, bagan, light emitting diode, Palabuhanratu, lampu celup